Labour market efficiency, technological readiness, financial access, cost of remittance, and educational attainment, on financial development in Africa: A moderating effect of political stability - Nambie, Nicholas Bamegne; Haywood-Dadzie, Dorcas Oye; Ayertey, James Narh (International journal of economic perspectives, 2024)
The objective of this study is to analyse the impact of educational attainment, technological proficiency, labour market efficacy, and financial accessibility on the progress of financial development in Africa. The research utilized a two-step system generalized method of moments (GMM) estimator, ordinary least square method, and random effect model to analyse panel data pertaining to African countries from 2002 to 2023. Consideration is given to the moderating effect of political stability on the model variables. Financial development in Africa is significantly and positively correlated with labour market efficiency, financial access, technological readiness, and educational attainment, according to the study’s findings. Furthermore, there exists a substantial relationship between the moderation effect of political stability and each of the independent and dependent variables. Policymakers are advised to enact comprehensive regulatory reforms in order to guarantee the stability, transparency, and inclusivity of the financial system. Policy makers may also allocate resources towards enhancing the capabilities of regulatory bodies and financial institutions, concurrently encouraging the growth and implementation of digital financial services, including e-wallets and mobile banking. Further investigation is warranted regarding the utilization and implementation of mobile money, and digital payment systems.